Sad Kerthi as a Legal Concept of Self-Determination for Indigenous People in Bali - Prasada, Dewa Krisna; Nurjaya, I Nyoman; Sulistyarini, Rachmi; Muktiono, Muktiono (Serikat Pengajar Hak Asasi Manusia Indonesia, 2024)
This study aims to examine the historical and cultural aspects of Sad Kerthi as a legal terminology that is part of the traditional knowledge of indigenous people in Bali, one of Indonesia’s culturally richest provinces. The recognition and respect for indigenous communities have been a significant topic outlined in Article 18B paragraph (2) of the 1945 Constitution. This Article underpins legislations and regulations aimed to empower indigenous communities to exercise self-governance in their social context within the framework of the contemporary globalised society. By using socio-legal research methods with a statute approach and legal facts, this research finds that the lack of a legal definition of Indigenous people adversely impacts the self-determination of Indigenous people in Indonesia. At the same time, the common problems faced are not unequivocal, by considering Bali, Sad Kerthi as local wisdom is incorporated in Bali Province Act 15/2023. This legislation is further broken down into local regulations that allow Balinese communities to preserve their social structures and self-determination in everyday activities. Based on legal evidence collected from three different types of customary villages in Bali, which are Baliaga, Apanage, and Anyar, the indigenous communities in each of these traditional villages are autonomous and enjoy specific privileges maintained since their ancestors.